Online Learning Management to Improve Student's Cognitive Ability (Case Study at SMA Negeri 3 Seram West) - Sophia. S. Puttileihalat; R Kempa; P. Rahabav (Peneliti.net, 2022)
At the beginning of March 2020, in Indonesia the learning process on the formal route was disrupted and could not take place properly due to the emergence of the corona virus outbreak. Anticipating the wider spread of the virus, the government issued an online. The online learning process at SMA Negeri 3 Seram Barat leaves various problems starting from the planning, implementation and evaluation stages of learning. Based on these problems, the research aims to: 1) analyze the online learning planning process that can improve students' cognitive abilities at SMA Negeri 3 Seram Barat? 2) analyze the process of implementing online learning that can improve students' cognitive abilities at SMA Negeri 3 Seram Barat? 3) analyze the process of evaluating online learning that can improve students' cognitive abilities at SMA Negeri 3 Seram Barat? and 4) What are the supporting and inhibiting factors at the planning, implementation and evaluation stages of online learning?. This research is a qualitative type of research. The research subjects were 8 people. The instruments used were: interview guide, observation, and documentation. The data analysis technique used is descriptive-qualitative. The results of the study show that online learning begins in early March 2020. In 2021, teachers are generally equipped with learning tools, including: a simplified curriculum during the Covid-19 period and lesson plans issued by the Maluku Provincial Education and Culture Office. The planning documents that are owned are the Covid Emergency Curriculum, lesson plans, and teaching materials, to be given to students. At the stage of implementing the teacher's learning using zoom free is limited to only 30 minutes. The learning approach used is the scientific approach. Some teacher barriers are difficult to conduct a comprehensive learning assessment, the accentuation of the assessment is only on cognitive abilities.